CONCRETIZATION OF LAW: LEGAL FORMS - Xenia Dovgan (RUDN Journal of Law, 2020)
Stability and quality of legislation is checked by time. The organic development of law and the elements of the legal system ensures the protection of the fundamental rights and freedoms of a human and a citizen. In the current living conditions, especially in the period of serious epidemiological upheavals, the effectiveness of the adopted legal acts acquires significant value. This is overwhelmingly important during the period of the legislation update. The effectiveness and unity of legal regulation allows to evaluate the framework legislation. We examine the legislative forms of concretization of the framework legislation at different levels of legal regulation. The research methodology is determined by its sources. The use of the formal legal research method allowed us to analyze legal acts within the system. One of the main mechanisms for implementing the framework legislation is concretization, which enhances balancing law-making, law implementation and law enforcement activities. Due to a certain degree of generalization and abstractness alongside with the direction of legal regulation, key messages, defined at the level of the framework act, are being detailed and concretized in the subordinate act. Considering technical and legal factors, we can trace certain uncertainty created by legislator as a means to regulate new social relations and specify them at a subsequent level of legal regulation, taking into account temporary, socio-economic, procedural, ideological and other criteria.